Sunda Kelapa Port: a Case Study on Tourist Loyalty Building Through Destination Image, Tourist Motivation, and Perceived Value of Tourism Satisfaction - Septikache, Dian; Suhud, Usep; Rahmi, Rahmi (LPPPIPublishing, 2024)
The purpose of this research is to determine the influence of destination image, tourist motivation, perceived value, and tourist satisfaction on tourist loyalty to Sunda Kelapa Port. The research method uses a quantitative research design by distributing questionnaires. A total of 256 respondents were sampled using purposive sampling technique. The research objects in this study were respondents aged 18-65 years and had visited Sunda Kelapa Port at least three times in the past year. This research uses SPSS version 23 software and SEM (Structural Equation Model) from AMOS software to analyze and process research data. The research results show that: first, destination image, tourist motivation, and perceived value have a positive and significant effect on tourist satisfaction. Second, perceived value and tourist satisfaction have a positive and significant effect on tourist loyalty. Third, destination image and tourist motivation has no influence on tourist loyalty.